2012
DOI: 10.7314/apjcp.2012.13.12.6011
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's Esophagus and β-carotene Therapy: Symptomatic Improvement in GERD and Enhanced HSP70 Expression in Esophageal Mucosa

Abstract: Introduction: Epidemiological studies suggest a protective role for β-carotene with several malignancies. Esophageal adenocarcinoma frequently arises from Barrett's esophagus (BE). We postulated that β-carotene therapy maybe protective in BE. Materials and Method: We conducted a prospective study in which 25 mg of β-carotene was administered daily for six-months to six patients. Each patient underwent upper endoscopy before and after therapy and multiple mucosal biopsies were obtained. Additionally, patients c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Higher fruit and vegetable intake and higher beta-carotene intake have been associated with reduced EAC risk (4,45). Additionally, beta-carotene therapy was shown to ameliorate GERD symptoms (46). Bacterial biosynthesis of siderophores (iron-chelating compounds) was associated with higher EAC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Higher fruit and vegetable intake and higher beta-carotene intake have been associated with reduced EAC risk (4,45). Additionally, beta-carotene therapy was shown to ameliorate GERD symptoms (46). Bacterial biosynthesis of siderophores (iron-chelating compounds) was associated with higher EAC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that carotenoids have antioxidant, anti-apoptotic, and anti-inflammatory properties27. In the esophagus, long-term β-carotene therapy has been shown to be beneficial in both patients with GERD and BE28. Further, epidemiological studies have found that an increased intake of β-carotene was associated with a decreased risk of BE629.…”
Section: Discussionmentioning
confidence: 99%
“…Barret's esophagus. In fact we have previously demonstrated in our study that β-carotene therapy reduced the mean length of Barret's segment and also caused restoration of histological and molecular changes in esophageal mucosa of patients with Barret's esophagus (Dutta et al, 2012). Thus, by targeting the HEE cells, carotenes may serve as an important preventive modality for esophageal cancer.…”
Section: Discussionmentioning
confidence: 54%
“…3HTdR uptake was performed using a modification of the method described previously (Dutta et al, 2012). On the day of the experiment, HEE/HESC cells were incubated with or without various concentrations of α-carotene, β-carotene, or a combination of α-and β-carotene, respectively, for 20 h at 37 o C in a CO 2 incubator for different periods of time (Days 1,3,5,7,9,11,15).…”
Section: H Thymidine ( 3 H Tdr) Uptake Assaymentioning
confidence: 99%